Infrared observation of OC-C2H2, OC-(C2H2)2 and their isotopologues. (17th December 2018) - Barclay, A. J.; Mohandesi, A.; Michaelian, K. H.; McKellar, A. R. W.; Moazzen-Ahmadi, N.
ABSTRACT: The fundamental band for the OC-C2 H2 dimer and two combination bands involving the intermolecular bending modes ν9 and ν8 in the carbon monoxide CO stretch region are re-examined. Spectra are obtained using a pulsed supersonic slit jet expansion probed with a mode-hop free tuneable infrared quantum cascade laser. Analogous bands for OC-C2 D2 and the fundamental for OC–DCCH as an impurity are also observed and analysed. A much weaker band in the same spectral region is assigned to a new mixed trimer, CO-(C2 H2 )2 . The trimer band is composed uniquely of a -type transitions, establishing that the CO monomer is nearly aligned with the a -inertial axis. The observed rotational constants agree well with ab initio calculations and a small inertial defect value indicates that the trimer is planar. The structure is a compromise between the T-shaped structure of free acetylene dimer and the linear geometry of free OC-C2 H2. A similar band for the fully deuterated isotopologue CO-(C2 D2 )2 confirms our assignment. GRAPHICAL ABSTRACT: